Answer is =-1
implifying
-2x + 3 = -3x + 2
Reorder the terms:
3 + -2x = -3x + 2
Reorder the terms:
3 + -2x = 2 + -3x
Solving
3 + -2x = 2 + -3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3x' to each side of the equation.
3 + -2x + 3x = 2 + -3x + 3x
Combine like terms: -2x + 3x = 1x
3 + 1x = 2 + -3x + 3x
Combine like terms: -3x + 3x = 0
3 + 1x = 2 + 0
3 + 1x = 2
Add '-3' to each side of the equation.
3 + -3 + 1x = 2 + -3
Combine like terms: 3 + -3 = 0
0 + 1x = 2 + -3
1x = 2 + -3
Combine like terms: 2 + -3 = -1
1x = -1
Divide each side by '1'.
x = -1
Simplifying
x = -1
For the first one it’s 9490 & for the second it’s 860
Answer:
30p + 25
Step-by-step explanation:
I hope this helps.
Answer:
272.5 m²
Step-by-step explanation:
1/2x4x9=18
(9+18)/2=13.5. 13.5x11=148.5
(18+14)/2=16. 16x7=112
12+148.5+112= 272.5
Answer:
Step-by-step explanation:
Let the rate of boat in still water be b and the speed of the current be c
- Speed downstream = b + c
- Speed upstream = b - c
<u>We got equations for time:</u>
- 108/(b - c) = 3 ⇒ b - c = 36
- 108/(b + c) = 2 ⇒ b + c = 54
<u>Add up the equations:</u>
- b - c + b + c = 36 + 54
- 2b = 90
- b = 45 km/h
<u>Then finding the values of c</u>